High precision processing of flexible P3HT/PCBM modules with geometric fill factor over 95% - Kubis, Peter; Lucera, Luca; Machui, Florian; Spyropoulos, Georgios; Cordero, Johann; Frey, Alfred; Kaschta, Joachim; Voigt, Monika; Matt, Gebhard; Zeira, Eitan; Brabec, Christoph (Organic Electronics, 2014)
Flexible OPV modules, based on P3HT:PCBM as absorber layer, were manufactured with a power conversion efficiency over 3% and for a total area of 3500 mm(2) consisting of 14 in series interconnected cells. The modules utilize the excellent mechanical and the outstanding optical properties of sputtered transparent ITO-Metal-ITO (IMI) electrodes deposited on the PET foil on the one hand, and the combination of large area slot-die coating with high resolution ultrafast laser patterning on the other hand. The manufacturing of modules with outstanding performance was found to be reproducible. The right combination of innovative electrodes and smart roll-to-roll compatible processing technologies demonstrates a viable path towards high efficient industrial module technology. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Flexible transparent electrode; Flexible OPV module; Slot-die coating; Ultra-fast laser patterning; High geometric fill factor